Geoprocessamento aplicado ao estudo de viabilidade ambiental de áreas para implantação de aterro sanitário na bacia hidrográfica do Rio Uraim no município de Paragominas - PA - SOUSA, Sâmio Costa de (2019)
The final disposal of solid waste is one of the biggest environmental problems in the cities where the most common is the simple deposition in inappropriate places, causing many environmental and public health problems. Even to cities that propose to perform an adequate final destination, such as landfill site, selecting a viable area for this finality is a very complex problem due to multiple criteria to be considered. In this scenario, the geotechnologies introduced themselves as viable tools for facilitating the analysis of a lot of geographic phenomena, allowing environmental modeling of physical and biotic resources, human occupation and their interrelationships. In this context, we performed to multicriteria analysis by means of geotechnologies using the method of Analytical Scanning and Integration Locational to jointly analyze the characteristics of geomorphology, hydrography, infrastructure, soil types and land use and occupation, with objective of identify areas suitable for the implantation of landfill sites in watershed of Uraim River, where is located the seat of the city of Paragominas (PA). The end result of this study is a map with the classification of areas of the watershed of the Uraim River about the viability of the landfill site facility. In the result it was verified a large availability of areas suitable for the study purpose. In addition, the results described can be used as an important tool in municipal solid waste management, to provide the municipality a list of potentially viable areas options for disposal of waste.